Platinum Dissolution in Realistic Fuel Cell Catalyst Layers. (9th March 2021) - Ehelebe, Konrad; Knöppel, Julius; Bierling, Markus; Mayerhöfer, Britta; Böhm, Thomas; Kulyk, Nadiia; Thiele, Simon; Mayrhofer, Karl J. J.; Cherevko, Serhiy
Abstract: Pt dissolution has already been intensively studied in aqueous model systems and many mechanistic insights have been gained. Nevertheless, transfer of new knowledge to real‐world fuel cell systems is still a significant challenge. To close this gap, we present a novel in situ method combining a gas diffusion electrode (GDE) half‐cell with inductively coupled plasma mass spectrometry (ICP‐MS). With this setup, Pt dissolution in realistic catalyst layers and the transport of dissolved Pt species through Nafion membranes were evaluated directly. We observed that 1) specific Pt dissolution increased significantly with decreasing Pt loading, 2) in comparison to experiments on aqueous model systems with flow cells, the measured dissolution in GDE experiments was considerably lower, and 3) by adding a membrane onto the catalyst layer, Pt dissolution was reduced even further. All these phenomena are attributed to the varying mass transport conditions of dissolved Pt species, influencing re‐deposition and equilibrium potential. Abstract : An in situ technique is presented that closes the gap between catalyst degradation studies in real devices and fundamental electrochemical analyses. The method involves direct measurement of platinum dissolution in realistic catalyst layers and through Nafion membranes. The impact of catalyst loading and electrode–electrolyte interface on platinum dissolution, as well as transport behavior of dissolved Pt species through Nafion membranes, are investigated.